The Influence of Brand Ambassadors and Flash Sale Events on the Lazada App on Impulse Buying in the Cirebon Region - Rosmaningsih, Devi Evian; Rajasmara, Prasasti; Ardhika , Yulian; Rahmadi (Indonesian Journal of Business Analytics, 2024)
Technological developments have produced many things, one of which is e-commerce or an online marketplace, one of which is Lazada. The purpose of this study was to measure how much influence brand ambassadors (X1) and flash sales (X2) have on impulse buying (Y) in lazada applications in the Cirebon area. This research method uses probability sampling techniques with simple random sampling methods and conducts a sample of 100 respondents with age criteria 17-25 years of lazada application users in the Cirebon area. The SPSS 24 software application helps in analysing data which includes instrument tests, classical assumption tests, and multiple linear regression tests. From the test results, it can be concluded that the brand ambassador and flash sale variables have a positive and significant effect on impulse buying.